Snowmobiles parked at the "Vue de l'Ile" lounge - Power, Sheena (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Interview with Anastasia Lainey 'Growing up in Mainland' March 12/90 ». -- Photo is one of a series associated with a Memorial University folklore student term paper: " Interview with Anastasia Lainey 'Growing up in Mainland' March 12/90".